The use of change theory to facilitate the consolidation of two diverse Bachelors of Science in Nursing programs. - Pawl, Jean D.; Anderson, Lori S. (Nursing Outlook)
Background Consolidation of resources, programs, and even universities are measures that university systems consider for economic reasons. The transformation and restructuring of two diverse nursing programs utilized an organizational change tool to guide the consolidation efforts. Purpose Insights on how to use an organizational change model and lessons learned are shared for higher education units that may face consolidation. Methods The ADKAR Change Management Model, one of many organizational change resources, was advantageous in consolidating two diverse nursing programs when two universities were mandated to become one. Conclusions Change is inevitable yet when faced with transition and transformation, thoughtful and strong, committed leaders who portray open transparent communication are an absolute requirement for sustained change. To guide the process, the ADKAR Change Management Model is an insightful and worthwhile resource.